2012
DOI: 10.1111/j.1464-410x.2012.10946.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of tyrosine kinase inhibitors in patients with metastatic kidney cancer receiving haemodialysis: a retrospective Italian survey

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Sunitinib and sorafenib are orally administered multikinase inhibitors approved for the treatment of advanced RCC. The limited pharmacokinetics data on sunitinib and sorafenib suggest that haemodialysis does not significantly alter plasma concentrations. In this retrospective study we define the safety and efficacy of tyrosine kinase inhibitors in patients with metastatic RCC (mRCC) and end‐stage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Outcomes compared with patients with normal kidney function were similar with a reported median progression-free survival (PFS) of 10.3 months and a median OS of 22.6 months. 9 We similarly found sunitinib and sorafenib to be well tolerated, with no Grade 4 toxicities reported. In our study, patients had a median PFS of 5.6 months with sunitinib treatment and 4.2 months with sorafenib treatment.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Outcomes compared with patients with normal kidney function were similar with a reported median progression-free survival (PFS) of 10.3 months and a median OS of 22.6 months. 9 We similarly found sunitinib and sorafenib to be well tolerated, with no Grade 4 toxicities reported. In our study, patients had a median PFS of 5.6 months with sunitinib treatment and 4.2 months with sorafenib treatment.…”
Section: Discussionmentioning
confidence: 55%
“…Masini and colleagues conducted a retrospective study of 24 patients with mRCC who were treated with sunitinib (16 patients) or sorafenib (8 patients). 9 Both TKIs appeared to be safe with no unexpected adverse outcomes noted. Outcomes compared with patients with normal kidney function were similar with a reported median progression-free survival (PFS) of 10.3 months and a median OS of 22.6 months.…”
Section: Discussionmentioning
confidence: 90%
“…The median number of target therapy per patient is 3, with a median duration of treatment of 28 months [19]. Masini et al also reported a multicentric retrospective Italian study evaluating the outcome of patients treated with sunitinib and sorafenib in this setting [20]. The findings agree with each of them showing that tyrosine kinase inhibitors appear to be effective and safe in patients with mRCC and ERSD who were receiving dialysis.…”
mentioning
confidence: 80%
“…Studies based on the limited number of patients seem to suggest that concomitant use of sunitinib and dialysis is feasible with good results 1921. Furthermore, it was suggested that hemodialysis did not significantly alter plasma concentrations of sunitinib 2224. Although other grade ≥3 toxicities have been reported with concomitant dialysis and sunitinib (mainly hypertension),23,25 we report here, for the first time, related-to-dialysis-and-sun itinib vomiting.…”
Section: Discussionmentioning
confidence: 70%